Analisis Kesalahan Imlaiyyah pada Abstrak Tesis Mahasiswa Magister PBA UIN Maulana Malik Ibrahim Malang Perspektif Kaidah Imla - M Sholih Salimul Uqba; Danial Hilmi; Ummu Sulaimah Saleh; Evy Nur Rohmawaty (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The objective of this study is to provide a detailed description of the types of Imlaiyyah errors present in the abstracts of Master of Arabic Language Education theses submitted by students at UIN Maulana Malik Ibrahim Malang. This research employs a descriptive qualitative method with a content approach to language errors and documentation as a data collection technique. The data sources for this research are the thesis abstracts of Master of Arabic Education students at UIN Maulana Malik Ibrahim Malang, which serve as the primary sources, and articles and books on Imlaiyyah, which serve as the secondary sources. The study sample consisted of 30 randomly selected abstracts from e-theses published in 2024. The analysis of Imlaiyyah errors was conducted in accordance with the methodology proposed by Corder, which were then explained and evaluated. The findings indicate that Imlaiyyah errors persist in the thesis abstracts of Master of Arabic Language Education students at UIN Maulana Malik Ibrahim Malang. The types of Imlaiyyah errors identified include the following: (1) errors related to the writing of the hamzah, (2) errors related to the writing of the al, (3) errors related to the writing of the ta', (4) errors related to the writing of the hijaiyyah letter, and (5) errors related to the writing of the harakat. Additionally, several factors were found to affect the occurrence of these errors and the evaluation of their severity.